ANALISIS PERAN UNIT PELAKSANA TEKNIS KEMENTERIAN LINGKUNGAN HIDUP DAN KEHUTANAN DALAM DESENTRALISASI KEHUTANAN - Handoyo Handoyo; Andri Setiadi Kurniawan (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2018)
The role of Technical Implementing Unit (TIU) is one of prominent issues of decentralization. A study was carried out to identify decentralization issues in South Sulawesi and East Java Provinces as well as to measure stakeholder attitudes towards the existence of TIU. The results showed that the existance of BKSDA, BTN, BPA, BPKH, and Balai Diklat LHK are recognized importantly. Meanwhile, BPHP and BPDASHL are considered to be less important in the region because their functions and authorities can be delegated to the provincial and regent/city governments. Similiar recognition applied to BPTH and Balai Litbang LHK. The emerging issue of decentralization in East Java is the placement of local officials which is inconsistent with their competence, lacking of funding from APBD for forestry developmentt, high demand from public to be enganged in the management of the forest, and overlapping authority. Meanwhile in South Sulawesi the capacity of local forestry agencies are impaired, authority is misused, and consolidation of the region is delayed, ego among vertical instituions ego and poor coordination. Based on the indicator of good forest governance, it is measured that the attitude of stakeholders and organizational capacity in East Java and South Sulawesi is neutral and good respectively.